A transitividade : da visão tradicional ao funcionalismo - Oliveira, Aline Moraes (2009)
This dissertation reports on the transitivity’s phenomenon. At first, it presents, on the whole, the studies in liguistic and a brief historic overview. It operates with on the language and transitivity functionalist perspective. On at this work, we intend to do a counterpoint between the tradicional, valencial and functional (north-american) approaches on transitivity treatment, we highlight the relevance of the last one, by passages analysis and studies in linguistic, as one. The north-american perspective considers the transitivity not as a intrisec property of the verb like a lexical unit, but as a complex consisting of ten regardless semantic-sintatic parameters (HOPPER & THOMPSON,1980), that focuses on diferent views of the transference of the action on a different part of the sentence. The object in analysis is formed by opinion reports written by highschool’s and college’s informants, e.o., the informants are eighteen years old or over. The reports are part of the collected and organized texts by the Dicourse and Grammar Studies (DG). The studies of that group include the cities of Rio de Janeiro, Rio Grande, Natal, Juiz de Fora and Niterói; however, in this work, we focus on the texts that are made by the informants of the Rio de Janeiro. The idea of type/genre of the text and its relation during the process of text’s meaning construction and the low or high transitivity, e.o., of the informational status. The sentences of the narratives that were analyzed by Hopper and Thompson (1980) were noticed like they represent a different behavior from the opinion reports reported at this dissertation.